A first course in the finite element method - Logan, Daryl L. (Cengage Learning, 2011)
Offering an approach to the finite element method that can be understood by both undergraduate and graduate students, this book is suitable as a basic learning tool for the undergraduate student in civil and mechanical engineering whose focus is on stress analysis and heat transfer.